Pediatric Trauma Audit and Outcome of Limb Fractures in Children (Journal of Pakistan Orthopaedic Association, 2014)
Objectives: To audit the pediatric trauma and evaluate the outcome of fracture management and formulate preventive measures to decrease trauma in children.Material and method: This study was conducted from July 2012 to June 2013. Children with traumatic injuries were admitted to the unit and prospectively studied. Data collection was done in a prescribed proforma.Results: Total of 940 children with orthopedic trauma received out of which 869 had fractures and 71 had soft tissue injuries. Most of the fractures were close 854 while 15 were open fractures. Upper limb fractures accounted for 73% of the cases. Fractures sustained from falls were 513 (59%) and from road traffic accidents 301 (35%) and sports injuries were 46(5%). Most of the fractures (86% of total cases) were treated conservatively with MUA and pop or traction. A particular problem was identified in the audit; risk of displacement of displaced fractures of the upper limb, which were managed conservatively, was quiet high i.e. 17%. On the other hand there was no revision done in those managed with open reduction internal fixation.Conclusion: Pediatric trauma is associated with high morbidity, preventive measures at community and national level should be taken to educate the parents and children. A more specialized supervision of primary treatment of pediatric trauma is required to decrease the rate of readmission and reoperation.